UNCERTAINTY IN THE RICE SUPPLY CHAIN DURING PRE AND POST PANDEMIC - A CROSS CASE OF AGRICULTURAL COOPERATIVES IN INDONESIA - Rosyadi, Rosyadi; Wijaya, Adi (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
Even though the social order is starting to recover from the risk of Covid-19 transmission, but the performance of food security is still constrained in some countries, including Indonesia, where the majority of the population consumes rice. If the infection rate spikes again, it can hamper the supply chain for food commodities such as rice. From this paper, the research target focuses on the structure of the supply chain in rice under government supervision operated by a national company. In distribution capacity, domestic rice is a local type of superior quality to every interisland agricultural cooperative in Indonesia. Overall, this scientific paper calculates the multidimensional disruption in the rice supply chain from across the major islands in Indonesia During a normal situation and after a pandemic. A series of annual report data sourced from the Central Bureau of Statistics (BPS) are tabulated using parametric regression. The research sample is framed in a combination of agricultural cooperatives in 6 objects in Indonesia based on 12 key variables. The time panel is divided into two compositions: 2017–2019 (pre–Covid) and 2020–2022 (post–Covid). The output of the study clarifies that there is a significant relationship between pre–Covid and post–Covid to the manufacturing industry, quality control, logistics, land infrastructure, and sales significantly. Then, there was a significant link between pre–Covid and post–Covid from paddy production to the manufacturing industry mediated by supply, logistics to agricultural cooperatives mediated by land and marine infrastructure, then agricultural cooperatives to consumers mediated by sales. In relation to this research, the participation of stakeholders is suggested to adopt schemes and controls that are integrated with the transition of the rice supply chain.